Analisis Struktur, Perilaku dan Kinerja Pasar Rumput Laut di Kabupaten Konawe Selatan - Badriadi Badriadi; Ine Fausayana; La Nalefo (Jurnal Sosio Agribisnis, 2020)
This study aims to determine the pattern of marketing channels, analyze the structure, behavior and performance of the seaweed market in Konawe Selatan Regency. The population in this study are all marketing actors and farmers who carry out seaweed farming activities. The determination of the sample of seaweed farmers was carried out using the Cluster Random Sampling method, while the sampling of marketers was carried out using the Snowball Sampling technique. The number of samples of marketing actors was 12 people, and the number of samples of farmers was 162 farmers or 20 percent of the population. The structure of the seaweed market is known by an analysis of market share, CR4 (concentration ratio for biggest four), barrier to entry. Market behavior approach is carried out by descriptive analysis with regard to the market which is the object of study. Meanwhile, the market performance approach uses marketing margin analysis and farmer's share analysis. The results of the study indicate that the marketing channels for seaweed in Konawe Selatan Regency consist of 3 patterns. The percentage of sales volume in pattern 1 is 29 percent, pattern 2 is 14 percent, and pattern 3 is 57 percent. The seaweed market structure at the collector and exporter level is oligopsony, while the seaweed market structure at the wholesaler level is monopsony. Market behavior uses a mechanism based on a form of mutually binding cooperation and the dependence of fishermen / farmers on capital loans. This causes the bargaining position of fishermen / seaweed farmers to become weak so that fishermen / farmers only act as price takers. Market performance analysis can be seen from the indicators, namely marketing margin and farmer's share. Even though the market is in an imperfect competitive market mechanism due to the existence of a relatively long cooperation bond that creates market dominance by buyers, based on the results of the farmer's share analysis it can be said that all marketing channels of seaweed are efficient because the share of the price received by farmers is greater than 50 percent.Key words: seaweed marketing; market structure; market behavior; market performance